Impact of physiotherapy with telerehabilitation on caregivers of patients with neurological disorders: A systematic review protocol - Silva, Emília Márcia Gomes de Souza e; de Melo, Luciana Protásio; de Souza, Aline Alves; de Holanda, Ledycnarf Januário; Ribeiro, Tatiana Souza; Valentim, Ricardo Alexsandro de Medeiros; Lindquist, Ana Raquel (Frontiers in Aging Neuroscience, 2022)
Introduction: Caregivers are essential during and after rehabilitation but exhibit intense physical and mental burdens due to responsibilities, resulting in stress, irritability, depression, anxiety, pain, and financial distress. Telerehabilitation offers several remote health services that improve time, engagement, and physical and mental health care access. Thus, we outlined a systematic review protocol to evaluate the impact of telerehabilitation on the burden, stress, pain, and quality of life of caregivers of patients with neurological disorders. Methods: Searches will be conducted in Ovid MEDLINE, Pubmed, Scopus, Web of Science, Embase, Cochrane Central Register of Controlled Trials, Physiotherapy Evidence Database, and PsycINFO databases. Clinical trials evaluating the burden, stress, pain, and quality of life of caregivers of patients with neurological disorders using telerehabilitation will be included without publication date or language restriction. Two reviewers will independently select studies from titles, abstracts, and reference lists. The quality of evidence and risk of bias will be assessed according to Cochrane recommendations. Results: This systematic review to be developed will evaluate the impact of telerehabilitation on the burden, stress, pain, and quality of life of caregivers of patients with neurological disorders. Discussion: Caregivers, especially of patients with neurological disorders, need more attention since the overload, stress, duties with other personal responsibilities, and low remuneration may impact the quality of life. Therefore, they need intervention, especially physical therapy via telehealth, which values the time of caregivers and may change their perception of health and quality of life. PROSPERO registration number: CRD42022278523